DNA methylation dynamics, metabolic fluxes, gene splicing, and alternative phenotypes in honey bees - Foret, Sylvain; Kucharski, Robert; Pellegrini, Matteo; Feng, Suhua; Jacobsen, Steven E.; Robinson, Gene E.; Maleszka, Ryszard (Proceedings of the National Academy of Sciences - PNAS, 2012)
In honey bees (Apis mellifera), the development of a larva into either a queen or worker depends on differential feeding with royal jelly and involves epigenomic modifications by DNA methyltransferases. To understand the role of DNA methylation in this process we sequenced the larval methylomes in both queens and workers. We show that the number of differentially methylated genes (DMGs) in larval head is significantly increased relative to adult brain (2,399 vs. 560) with more than 80% of DMGs up-methylated in worker larvae. Several highly conserved metabolic and signaling pathways are enriched in methylated genes, underscoring the connection between dietary intake and metabolic flux. This includes genes related to juvenile hormone and insulin, two hormones shown previously to regulate caste determination. We also tie methylation data to expressional profiling and describe a distinct role for one of the DMGs encoding anaplastic lymphoma kinase (ALK), an important regulator of metabolism. We show that alk is not only differentially methylated and alternatively spliced in Apis, but also seems to be regulated by a cis-acting, anti-sense nonprotein-coding transcript. The unusually complex regulation of ALK in Apis suggests that this protein could represent a previously unknown node in a process that activates downstream signaling according to a nutritional context. The correlation between methylation and alternative splicing of alk is consistent with the recently described mechanism involving RNA polymerase II pausing. Our study offers insights into diet-controlled development in Apis.